Cross-sectoral communication by bringing together patient with cancer, general practitioner and oncologist in a video-based consultation: a qualitative study of oncologists' and nurse specialists' perspectives. Issue 5 (5th May 2021) - Hansen, Dorte Gilså; Trabjerg, Theis Bitz; Sisler, Jeffrey James; Søndergaard, Jens; Jensen, Lars Henrik
Abstract : Shared care models in the field of cancer aim to improve care coordination, role clarification and patient satisfaction. Cross-sectoral communication is pivotal. Involvement of patients may add to intended mechanisms. A randomised controlled trial 'The Partnership Study' tested the effect of bringing together patient, general practitioner (GP) and oncologist for a consultation conducted by video. Purpose: As part of the process evaluation, this study aimed to explore experiences, attitudes and perspectives of the oncological department on sharing patient consultations with GPs using video. Methods: Four semistructured interviews with five oncologists and four nurse specialists were conducted in February 2020. We focused on the informants' experiences and reflections on the potential of future implementation of the concept 'inviting the GP for a shared consultation by video'. The analyses were based on an inductive, open-minded, hermeneutic phenomenological approach. Results: A total of six overall themes were identified: structuring consultation and communication, perceptions of GP involvement in cancer care, stressors, making a difference, alternative ways of cross-sector communication and needs for redesigning the model. The concept made sense and was deemed useful, but solving the many technical and organisational problems is pivotal. Case-specific tasks and relational issues were targeted by pragmatically rethinking protocol expectations and the usual way of communication and structuring patient encounters. Case selection was discussed as one way of maturing the concept. Conclusion: This Danish study adds new insight into understanding different aspects of the process, causal mechanisms as well as the potential of future implementation of video-based tripartite encounters. Beyond solving the technical problems, case selection and organisational issues are important. Acknowledging the disruption of the usual workflow, the introduction of new phases of the usual encounter and the variety of patient–GP relationships to be embraced may help to better understand and comply with barriers and facilitators of communication and sharing. Trial registration number: NCT02716168 .